ICTV Virus Taxonomy Profile: Rhabdoviridae 2022 - Walker, Peter J; Freitas-Astúa, Juliana; Bejerman, Nicolas; Blasdell, Kim R; Breyta, Rachel; Dietzgen, Ralf G; Fooks, Anthony R; Kondo, Hideki; Kurath, Gael; Kuzmin, Ivan V; Ramos-González, Pedro Luis; Shi, Mang; et al. (Journal of general virology, 2022)
The family comprises viruses with negative-sense (-) RNA genomes of 10-16 kb. Virions are typically enveloped with bullet-shaped or bacilliform morphology but can also be non-enveloped filaments. Rhabdoviruses infect plants or animals, including mammals, birds, reptiles, amphibians or fish, as well as arthropods, which serve as single hosts or act as biological vectors for transmission to animals or plants. Rhabdoviruses include important pathogens of humans, livestock, fish or agricultural crops. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family , which is available at ictv.global/report/rhabdoviridae.